Efeito do herbicida Roundup® sobre a estabilidade de membranas de eritrócitos de coelhos e de frangos - Batista, Maria Thereza Alves (2008)
Roundup® is the most used herbice in Brazilian agriculture. It contains in its composition the salt of glyphosate with isopropylammonium, beyond the surfactant polyoxy-ethyleneamine. This combination significantly increases the power of the herbicide glyphosate. Although the destination of the product is the control of weeds, he has great impact on the animal organisms. In this work, the hemolytic power of Roundup® was tested in blood samples from broiler chickens and rabbits, harvested in the presence of EDTA or heparin as an anticoagulant. The nature of anticoagulant used in the collection of blood interfered in the hemolytic action of Roundup®. The herbicide produced lysis of red blood cells of chickens and rabbits within the concentration range recommended by the manufacturer for use in agriculture. The red blood cells of broilers were more resistant than the red blood cells of rabbits against lysis induced by Roundup®.